Functional Behavioral Assessment for a Boy With Duchenne Muscular Dystrophy and Problem Behavior: A Case Study From Greece. (December 2013) - Theodoridou, Zoe; Koutsoklenis, Athanasios
This article focuses on the application of functional behavioral assessment (FBA) to design a positive behavior intervention (PBI) for a boy with Duchenne muscular dystrophy (DMD) who encounters serious difficulties at the mainstream school because of behavioral problems and physical limitations. After the definition of problem behavior and its causes, a number of environmental changes in the context of positive behavior support (PBS) aiming at learning outcome and social engagement were implemented. The assessment steps and the intervention are thoroughly discussed. This work expands the existing literature by highlighting the feasibility and applicability of FBA and PBS in a low-incidence population within a Greek classroom environment.